Training plan for entrepreneurs: imperative to strengthen microenterprises - Cabrera Toscano, Eduardo Fabricio (2023)
The article presented responds to the objective of  designing a training plan for entrepreneurs in the social sectors of the canton of La Maná, Cotopaxi, based on the identification of the main insufficiencies that exist in this regard and, from this, contribute to the creation of new economic models that have an impact on the consolidation of the democratic state, the solidarity and sustainable economic system that strengthens citizenship, to help promote the transformation of the productive matrix, the solidarity economy and sustainable development. A qualitative-quantitative study of a descriptive nature was carried out, through observation, surveys, interviews and review of economic records. Likewise, the search and analysis of specialized literature was carried out to compare the real and the desired state; On this basis, through theoretical modeling, the training plan is designed, in interrelation with the analytical-synthetic and inductivedeductive methods. In general, it is considered that the training plan aimed at entrepreneurs from the social sectors of the La Maná canton enables the success of a microenterprise with committed employees, througha series of activities that ensure competitiveness, reducing training costs, opportunity costs and costs of dissatisfied customers due to incorrect execution of the company’s processes.